Research on the capability, opportunity, and motivation of schools to conduct physical activities in China: a cross-group validation - Jingtao Wu; Yi Yang; Yanhong Shao; Xiaolin Zhang; Wanli Zang; Jun Hu (BMC Public Health)
Abstract Background Insufficient physical activity among adolescents is a major global public health concern, and schools are considered key venues for promoting physical activity. Teachers play a crucial role in the implementation of policies. This study adapted and validated the COM-PASS scale, based on the COM-B model, to assess its reliability and validity in the Chinese context. Methods This study validates the appropriateness of the COM-PASS scale based on the COM-B model, assessing its reliability and validity within the Chinese cultural context. A three-phase design was employed: (1) A Delphi method involving three rounds of surveys with 15 experts to refine the questionnaire's relevance and validity; (2) Cognitive interviews with 10 primary and secondary school teachers to evaluate item comprehensibility; (3) Confirmatory factor analysis of 4,033 questionnaires across China's seven major administrative regions to verify structural validity and internal consistency. Results The CFA results showed that the three-factor model fit well (χ2 = 3179.436, df = 518, CFI = 0.964, TLI = 0.956, RMSEA = 0.036), with factor loadings for all items exceeding 0.750. The Cronbach's α coefficients for the three dimensions were 0.957, 0.947, and 0.965, respectively. Path coefficient tests indicated strong explanatory power of the latent variables on the observed variables (standardized path coefficients ranged from 0.781 to 0.951). Cross-group validation demonstrated the scale's stability and applicability across different administrative regions in China. Conclusion The Chinese version of the COM-PASS scale has shown good reliability and validity among the population of Chinese primary and secondary school teachers, and it can effectively assess main factors affecting the development of school physical education activities. The results provide a targeted scientific basis for optimizing school physical education policies, addressing regional resource differences, and teacher training strategies. The scale demonstrates strong cultural applicability and provides practical guidance for enhancing the 'Double Reduction' policy and advancing school-based physical education activities across China.